PRACTICE AND PERSPECTIVES OF IMPLEMENTATION OF LAW STUDY COURSES IN FACULTIES OF LAW IN UNIVERSITIES OF APPLIED SCIENCES - Vilks, Andrejs; Kipane, Aldona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The dynamism of social processes, the continuous development of elements of the legal system, including innovations within the legal framework, the ongoing reform of law enforcement institutions and bodies, diversity of national and international legal practices, transformation of legal culture forms, including its deformations, define the need for developing of qualitative law study programmes (Bachelor, Master, PhD). Legal professionals need regularly to improve their legal knowledge and to ensure successive professional development. The qualitative implementation practice of study courses of law science and the prospects of their implementation are one of the key elements for the development of a democratic, legal and socially responsible state. Research aim: to identify the current practice of implementation of law science curricula and of study courses by modelling their potential development trends according to perspective social-economic development of society. Research methods: research of legal sources and literature, the Internet resources, modelling approach.